DIVERSITY OF MIGRATORY BIRDS IN SEVERAL TYPES OF WETLANDS (CASE STUDY IN SUMBERNADI VILLAGE, SOUTH LAMPUNG REGENCY) - Iswandaru, Dian; Maharany, Octavia Widya (Jurnal Nusa Sylva, 2025)
Bird migration is a natural phenomenon that plays a crucial role in maintaining global ecosystem balance. One of the most notable groups involved in this phenomenon is migratory waterbirds, which depend on wetlands as resting, feeding, and breeding sites during their migration period. This study aims to analyze the ecological indices of migratory birds, including species diversity, richness, evenness, abundance, and dominance, across various wetland types in Sumbernadi Village, South Lampung Regency. Data were collected from November to December 2024 using the point count method at six observation points representing four wetland types: mangrove, mudflat, fishpond, and rice field. The results recorded nine migratory bird species from three families, with the highest diversity observed in mudflats (H' = 1.958) and the lowest in mangroves (H' = 0.637). The Scolopacidae family dominated in terms of both abundance and distribution. Environmental factors, including food availability, vegetation structure, and human disturbance, influenced differences in diversity among habitats. These findings suggest that the wetlands in Sumbernadi Village provide vital ecological habitats for migratory birds. Therefore, sustainable management and conservation efforts are crucial for preserving the environmental functions of these wetlands and supporting the continuity of migratory bird populations in the region.